University of Florida Potato Variety Trials Spotlight: 'Atlantic' - Rodrick Z. Mwatuwa; Christian T. Christensen; Lincoln Zotarelli (EDIS)
This article introduces the potato variety, ‘Atlantic’, which was tested in trials at the University of Florida. ’Atlantic’ is a white-skinned, chipping potato commonly cultivated in Florida and resealed as a white mutant of the USDA breeding program. This 4-page fact sheet provides the general characteristics, season length and growth information, fertilization and planting instructions, as well as disease information for the potato variety, ‘Atlantic’. Written by Rodrick Z. Mwatuwa, Christian T. Christensen, and Lincoln Zotarelli, and published by the Horticultural Sciences Department, March 2016.